2011
DOI: 10.1063/1.3594579
|View full text |Cite
|
Sign up to set email alerts
|

Sub-nanosecond switching and acceleration to relativistic energies of field emission electron bunches from metallic nano-tips

Abstract: The authors explore the generation of short electron bunches from a field-emitter array cathode consisting of nanometer-sized metallic tips that is compatible with an acceleration electric field above 10 MV/m. Sub-nanosecond field emission electron bunches were generated by applying fast electrical pulses to an on-chip electron extraction gate electrode of the cathode. The subsequent acceleration of the field emission electron bunches to 5 MeV was demonstrated using the combined diode-RF cavity SwissFEL electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…In addition, a detailed comparison of the beam characteristics and the gate structures between FEA1 and FEA3 indicated that further improvement of the beam collimation can be achieved by optimizing the G ext aperture. The planar G col surface of our FEAs is likely to be advantageous for the operation in high acceleration electric fields of 10 MV/m and above 10,11 by reducing the probability of parasitic emission from the top surface and subsequent vacuum breakdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a detailed comparison of the beam characteristics and the gate structures between FEA1 and FEA3 indicated that further improvement of the beam collimation can be achieved by optimizing the G ext aperture. The planar G col surface of our FEAs is likely to be advantageous for the operation in high acceleration electric fields of 10 MV/m and above 10,11 by reducing the probability of parasitic emission from the top surface and subsequent vacuum breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Research on field emitter arrays (FEAs) has been actively pursued [1][2][3][4][5][6][7][8][9][10][11][12][13] with the aim of realizing high current and high current density cathodes, e.g., for compact microwave vacuum electronic amplifiers, such as traveling wave tubes (TWTs) [14][15][16][17] and compact free electron lasers. 7,18 FEAs are expected to help simplify the gun design and extend the operation range of such TWTs.…”
Section: Introductionmentioning
confidence: 99%
“…Also, by combining the initial pulsed acceleration with the following acceleration in RF cavities, the FEA electron beam was accelerated up to 5 MeV. 2 However, large energy spread was observed, because the FEA emission pulse was longer than one half of the RF acceleration cycle, equal to 333 ps; the pulse duration of the FEA pulse was evaluated to be equal to 390 ps from the RF phase dependent overlap of the field emission pulse. 4,5 Therefore, an order of magnitude shorter FEA pulses are required to utilize these FEAs as electron sources for accelerator applications such as free-electron lasers.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, a different approach was used to generate subnanosecond electrically gated electron pulses. 2,3 In these studies, FEAs with relatively high gate capacitance (200-400 pF) but with small substrate resistance below $10 À3 X ( Fig. 1) were used.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the available peak currents and provide integrated electron gun designs, tip sources can be combined into Spindt-type gated emitter arrays, [21][22][23][24] also providing the option of subnanosecond electronic gating. 25 While continuous field-emitter electron guns are now standard for static electron microscopy and crystallography applications, there is still much scope for the development of their phototriggered pulsed analogues, 14,25 particularly regarding the difficulty of incorporating and aligning optical elements in high electric field environments.…”
Section: Introductionmentioning
confidence: 99%